2018
DOI: 10.1016/j.biopsych.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Neurodevelopmental Disorders: The Promise of Regulatory Variation in the 3′UTRome

Abstract: Neurodevelopmental disorders have a strong genetic component, but despite widespread efforts, the specific genetic factors underlying these disorders remain undefined for a large proportion of affected individuals. Given the accessibility of exome sequencing, this problem has thus far been addressed from a protein-centric standpoint; however, protein-coding regions only make up ∼1% to 2% of the human genome. With the advent of whole genome sequencing we are in the midst of a paradigm shift as it is now possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 150 publications
(144 reference statements)
1
30
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) account for 2–3% of the total number of human genes, which mainly mediate gene silencing by binding to the 3′ untranslated regions (3′ UTR) of target miRNAs ( Wanke et al, 2018 ), make up an important and significant fraction of the regulation of various signaling pathways and biological processes in the repair of PNI ( Treiber et al, 2019 ). Recent researches suggested that miRNAs play an important role in PNI; hence, they have attracted increasing interest in peripheral nerve regeneration field ( Yu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) account for 2–3% of the total number of human genes, which mainly mediate gene silencing by binding to the 3′ untranslated regions (3′ UTR) of target miRNAs ( Wanke et al, 2018 ), make up an important and significant fraction of the regulation of various signaling pathways and biological processes in the repair of PNI ( Treiber et al, 2019 ). Recent researches suggested that miRNAs play an important role in PNI; hence, they have attracted increasing interest in peripheral nerve regeneration field ( Yu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Variants that affect non-coding regulatory regions of the genome may influence brain development and function via their critical role in regulating gene expression, and have been previously implicated in neurodevelopmental disorders (Wanke et al 2018 ). In this study, we hypothesised that de novo variation in 3′UTR regulatory regions may be a possible mechanism through which non-coding mutations contribute to ID.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable issues may arise with CSTF2's role in histone mRNA processing efficiency, affecting the cell cycle (Romeo et al, 2014;. These C/P changes subsequently affect post-transcriptional regulation of key mRNAs by changing 3 UTR regulation by revealing miRNA or RNA-binding protein sites, or by changing targeted localization of mRNAs to neural projections (Ciolli Mattioli et al, 2019;Fontes et al, 2017;Hafner et al, 2019;Jereb et al, 2018;Nazim et al, 2017;Taliaferro et al, 2016;Wanke et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mutations in mRNA processing genes encoding decapping enzymes (Ahmed et al, 2015;Ng et al, 2015), the polyglutamine binding protein 1 (PQBP1, Kalscheuer et al, 2003), spliceosomal proteins (Carroll et al, 2017), hnRNA-binding proteins (Bain et al, 2016), mRNA surveillance proteins (Tarpey et al, 2007), and cleavage and polyadenylation factors (Gennarino et al, 2015) cause intellectual disabilities. These disorders are associated with changes in the mRNA processing landscape, especially 3 end cleavage and polyadenylation (C/P), highlighting the importance of RNA processing in controlling neuronal function (Fontes et al, 2017;MacDonald, 2019;Szkop et al, 2017;Wanke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%